MODEL PENGEMBANGAN PEMBELAJARAN ANALISIS DAN PERANCANGAN SISTEM BERBASIS ONLINE PADA PERGURUAN TINGGI - Juman, Kundang Karsono (Lembaga Penerbitan Universitas Esa Unggul, 2018)
AbstractLess than optimal learning outcomes and the willingness of students in the lecture process are the problems that occur at this time. Learning process Information analysis and system design is one of the competencies in the development of supporting the competence of analysis and design of information systems. The methodology used is a learning model of analysis and design of multimedia-based information systems made through several stages, among others: Research and development / R & D Gall and Borg, instructional system design / ISD, model development models motivational learning (attention, relevance, confidient and relevance / ARCS). While the development of multimedia: development life cycle (system development life cycle / SDLC) and object oriented system design (OOAD). The output is a product learning system analysis and design of multimedia-based information systems that will be implemented in LMS learning. Furthermore this learning can be applied to higher education in Indonesia.Ã‚Â Keywords: Information Technology Project Management, multimedia, research and developmentÃ‚Â ABSTRAKKurang maksimal hasil belajar dan kemauanÃ‚Â mahasiswa dalam proses perkuliahanÃ‚Â adalah merupakan permasalahan yang terjadi pada saat ini. Proses pembelajaran Analisi dan perancangan sistemÃ‚Â Informasi adalah merupakan salah satu kompetensi di dalam pengembangan mendukung kompetensi analisis dan perancangan sistem informasi . Metodologi yang digunakan adalah Model pembelajaran analisis dan perancangan sistem informasiÃ‚Â berbasis multimedia yang dibuat melalui beberapa tahapan antara lain : Penelitian Pengembangan (research and development /R & D) Gall dan Borg, desain sistem pembelajaran (instructional system design/ISD), model pengembangan model pembelajaran motivasi (attention, relevance, confidient and relevance/ARCS). Sedangkan pengembangan multimedianya : siklus hidup pengembangan (sistem system development life cycle/SDLC) dan perancangan sistem berorientasi objek (object oriented analysis design/OOAD). Keluarannya adalah produk sistem pembelajaran analisis dan perancangan sistemÃ‚Â informasi berbasis multimedia yang akan dilaksanakan pada pembelajaran LMS. Selanjutnya pembelajaran ini dapat diterapkan pada pendidikan tinggi di Indonesia.Ã‚Â Ã‚Â Kata Kunci : Manajemen Proyek Teknologi Informasi, multimedia, penelitian dan pengembanganÃ‚Â